Phylogenetic study of the Hottarum Group (Araceae: Schismatoglottideae) utilising the nuclear ITS region - Low, S.L.; Wong, Sin Yeng; Jamliah, J; Boyce, P.C (Gardens' Bulletin Singapore, 2011)
Recent phylogenetic analyses of the tribe Schismatoglottideae (Araceae) elucidated a well-supported but internally unresolved crown group comprising Schismatoglottis sarikeensis (Bogner & M.Hotta) A.Hay & Bogner, previously placed in the genus Hottarum Bogner & Nicolson, the genus Phymatarum M.Hotta, and a number of species either novel or hitherto placed in Schismatoglottis Zoll. & Moritzi. The clade is particularly interesting in that it is centred in northern central Sarawak (Malaysian Borneo), north of the Lupar Divide and appears to represent an autochthonous radiation point for evolutionary activity isolated from the major tribal radiations in south-western Sarawak. Former Hottarum species (with the exclusion of H. truncatum) transferred to Piptospatha and Schismatoglottis are misplaced. All except Bakoa lucens (Bogner) P.C.Boyce & S.Y.Wong belong to this supra-Lupar Divide grouping. This study was undertaken to test the validity and phylogeny of the genus Hottarum utilising the nuclear ITS region.